Final answer:
To solve the given recurrence relations, we use the substitution method and solve for the unknown variables. The first recurrence relation, T(n) = 8T(n/2) + n^2, has a solution of T(n) = n^k + n^2. The second recurrence relation, x(n) = x(n-1) + n, has a solution of x(n) = n(n+1)/2.
Step-by-step explanation:
To solve the recurrence relation T(n) = 8T(n/2) + n^2, we can use the substitution method. Let's assume T(n) = O(n^k) for some constant k. Substituting this assumption into the recurrence relation, we get:
T(n) = 8T(n/2) + n^2 = 8(n/2)^k + n^2 = 8(n^k/2^k) + n^2.
Simplifying further, we get T(n) = n^k + n^2. Since this must hold for all n, we can equate the exponents and solve for k to find the value of k.
Plugging in the value of k in the assumed solution T(n) = O(n^k), we get the final solution for the given recurrence relation.
Using this procedure, we can similarly solve the second recurrence relation x(n) = x(n-1) + n. The solution for this recurrence relation is x(n) = n(n+1)/2.